Patients with Higher Pulse Wave Velocity Are More Likely to Develop a More Severe Form of Knee Osteoarthritis: Implications for Cardiovascular Risk - Tina Zavidić; Emina Babarović; Vedrana Drvar; Božena Ćurko-Cofek; Gordana Laškarin (Biomedicines)
Background/Objectives: Knee osteoarthritis (KOA) is a progressive degenerative joint disease characterised by low-grade inflammation and is associated with increased cardiovascular (CV) risk and arterial stiffness. Pulse wave velocity (PWV) is a quantitative measure of arterial stiffness and an important tool for detecting subclinical arterial calcification and CV risk. This study aimed to determine whether PWV can distinguish radiographically mild KOA (Kellgren–Lawrence grades 1-2) from severe KAO (Kellgren–Lawrence grades 3-4) in terms of CV risk factors. Methods: A total of 223 postmenopausal women with KOA participated in this cross-sectional study. Assessments included anthropometry, laboratory analyses, blood pressure and PWV measurements, a 6 min walk test, pain evaluation using a visual analogue scale (VAS), and completion of the International Physical Activity Questionnaire (IPAQ). Results: PWV was significantly higher in the severe KOA group (10.53 m/s vs. 8.78 m/s, p < 0.001). A cut-off value of 8.4 m/s effectively distinguished between severe and mild forms of KOA (AUC = 0.798, p = 0.001). OA grade, pain, age, waist circumference, WHR, SCORE 2/SCORE 2OP, systolic blood pressure, serum glucose, HbA1c, uric acid, creatinine, and erythrocyte sedimentation rate were increased in the group with PWV > 8.4 m/s, compared to the group with PWV ≤ 8.4 m/s. Conversely, eGFR, the 6 min walk test and physical activity of patients were reduced in the group with PWV > 8.4 m/s. A patient with a PWV > 8.4 m/s has a 1.77 times higher chance of developing a more severe form of the disease than a patient with a lower PWV. Conclusions: Patients with a higher PWV are more likely to develop a more severe form of KOA, which is associated with increased cardiovascular risk.